PERCEPTION OF TOURISM VOCATIONAL SCHOOL STUDENTS ON TOURISM DURING PANDEMIC AND ITS CORRELATION WITH THEIR DECISION TO STUDY IN TOURISM STUDY PROGRAM - Sukmadewi, Ni Putu Rika; Sutrisna, I Putu Edi; Dwi Lestari, Made Novita; Dane, Nyoman; Danendra Putra, Nyoman (Akademi Komunitas MAPINDO, 2022)
This study aims to determine and analyze the relationship between the perceptions of the Bali Tourism Vocational School students towards the tourism industry during the pandemic on making decisions to continue their studies in the tourism study program. From the research objectives, the research design will use a quantitative research approach. Thus, the Spearman correlation test is used to analyze the relationship between two variables in the form of ordinal data. However, to answer the formulation of the first and second problems, descriptive statistical tests are also needed to determine the characteristics and distribution of the data obtained. The perception of the Bali Tourism Vocational School students towards the tourism industry during the COVID-19 pandemic showed a positive trend, where as many as 82.2% of students had a positive perception of the tourism industry even though this industry experienced paralysis due to the prolonged brunt of the COVID 19 pandemic. From the results of the analysis, it was also found that the decision making of the Tourism Vocational High School students was very positive, where as many as 80.5% of the respondents revealed that they showed a tendency to strongly decide to continue their studies in the tourism study program. From the results of the hypothesis test, it is known that the perception of the Bali tourism vocational school students towards the tourism industry during the pandemic is positively correlated with a sufficient and significant level of relationship with students' decision making to continue their studies in the tourism study program. The magnitude of the contribution given by the perception variable of the Bali tourism vocational school students to the tourism industry during the pandemic on students' decision making to continue their studies in the tourism study program is 15.4%, while the other 84.6% contribution difference is given by other variables not examined in this study. Key words: Students’ descisson, students’ perception